On the Relation between Optimal Incentive Structures and the Cost and Benefits of Bottlenecks - Gietzmann, Miles; Hemmer, Thomas (Journal of Labor Economics, 2002)
We study optimal incentives for a two‐stage production process. First, we identify conditions under which the optimal incentive structure for both workers is based on total volume and conditions for when the final stage worker’s incentives are based on relative performance. We show that a bottleneck‐free and balanced line is optimal only when both workers’ contracts are based on volume, while it becomes desirable to limit the final stage worker’s productivity when his compensation is based on relative performance. Thus, we demonstrate that the benefit of removing bottlenecks hinges critically on the structure of the optimal incentive arrangement.